Propriedades de espuma no desempenho da flotação catiônica reversa de minério de ferro - Vanderson Eney de Matos (2022)
Reverse cationic flotation has been widely utilized in the concentration of iron ores. The efficiency of the process strongly depends on the characteristics of the froth phase which is function of the used system of chemical reagents. Frothers are surfactants responsible for the control of the froth properties by the reduction of the water surface tension, prevention of bubbles coalescence and froth stabilization. Collector and modifying agents perform different functions, but they also interfere on the froth properties interacting with frothers and acting at the different interfaces of the process. The objective of this study is to investigate the influence of reagents on the froth properties of the reverse cationic flotation of iron ore, by means of studies simulating the two-phase liquid-gas and three phase liquid-solid-gas interfaces, using fundamental and applied experiments. The structural formulas etherdiamine and ethermonoamine possess characteristics that induce distinct effects on froth formation and stability, justifying the difference in selectivity. The results demonstrated that etherdiamine imparts better floatability of pure quartz in microflotation tests at both concentrations and pH levels evaluated. In comparison with ethermonoamine, higher selectivity levels were achieved with etherdiamine in bench scale flotation of an iron ore. This superior performance was attributed to the greater metallurgical recovery of etherdiamine attributed to the lower hydrodynamic entrainment of fine hematite particles, caused by the formation of drier and more stable foams, overcoming the advantage of ethermonoamine to generate smaller bubbles. Besides that, there is a wide diversity of reagents that act exclusively as frothers. The combination of etheramine-specific frothers reagents potentiated flotation performance through improved selectivity. The replacement of etheramine by frothers, normally cheaper, presents better cost and benefit, however the combination between etherdiamine and ethermonoamine showed the best results.